Investment in Technologies: Key Strategy for Postharvest Loss Reduction - Mujuka, Esther; Ambuko, Jane; Mburu, John; Ogutu, Ackello (University of Nairobi, 2020)
Historically, horticultural research has focused on increasing productivity. However, given the inelasticity of scarce resources, there is a consensus that the focus should shift to PHL reduction. The high postharvest losses occur due to poor postharvest handling, lack of storage technologies, lack of processing facilities, and poor market access. Developing cold chains is critical in PHL. reduction in horticulture. However, conventional cold storage facilities required for proper cold chains are expensive and not applicable in most rural areas due to lack of electricity. Most households (>80%) in rural Kenya have no access to electricity making it untenable and costly to invest in cold storage facilities (GoK, 2008; Shitanda et al., 2011). Consequently, the lack of cold storage facilities to aggregate the perishable produce and negotiate for better prices predisposes the smallholders to exploitation by middlemen. Globally, applicable off-grid cold storage and processing technologies exist. However, their adoption in Kenya is limited due to a lack of awareness and demonstrated benefits. It is against this background, that the University of Nairobi’s postharvest project, with support from the Rockefeller Foundation’s YieldWise Initiative, sought to upgrade two fruit aggregation centres. Low-cost technologies including zero-energy brick coolers, evaporative charcoal coolers, and tunnel solar dryers were provided to create awareness and demonstrate their practical application. However, little is known about their economic impact in Kenya, hence this study.
Keywords: Kenya; Postharvest Loss